2019
DOI: 10.3390/clockssleep2010001
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Associations between Chronotype, Social Jetlag and Subjective Sleep Quality in Healthy Adults

Abstract: Social jetlag, a mismatch between internal biological time and social schedules, and a later timing of the midpoint of sleep on work-free days as an indicator of the circadian phase of entrainment (late chronotype), may be factors associated with poor quality sleep. This study examined the association of social jetlag and chronotype with subjective sleep quality ratings in a healthy young adult cohort and interrogated the moderating effects of sex and age on these associations. A total of 1322 participants age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…We observed an increase in subjective burden and a decrease in mental and physical wellbeing, which likely resulted from the exceptional situation due to the pandemic and was associated with decreased sleep quality and sleep duration. The strength of these effects may even have masked a link between reduced social jetlag and positive effects on sleep quality, which has previously been reported [8]. On a more positive note, we were also able to identify factors that limited the decline in sleep quality during the lockdown.…”
Section: Effects Of the Covid-19 Lockdown On Human Sleep And Rest-activity Rhythmsmentioning
confidence: 54%
“…We observed an increase in subjective burden and a decrease in mental and physical wellbeing, which likely resulted from the exceptional situation due to the pandemic and was associated with decreased sleep quality and sleep duration. The strength of these effects may even have masked a link between reduced social jetlag and positive effects on sleep quality, which has previously been reported [8]. On a more positive note, we were also able to identify factors that limited the decline in sleep quality during the lockdown.…”
Section: Effects Of the Covid-19 Lockdown On Human Sleep And Rest-activity Rhythmsmentioning
confidence: 54%
“…Given the intimate relationship between sleep quality and affect ( Konjarski et al, 2018 ), it is therefore not surprising that potential benefits from the reduction of social jetlag does not translate into increases in subjective sleep quality. Further, a recent study from our group recently reported only weak association between social jetlag and subjective sleep quality in a normative population ( Raman & Coogan, 2019a ). However, we did not record affective status in the current study, and as such we cannot directly test the relationships between changes in sleep timing, sleep quality and affect.…”
Section: Discussionmentioning
confidence: 83%
“…To describe the difference in sleep timing between weekdays and rest days, Wittmann and colleagues (2008) introduced the concept of social jet lag, usually more frequently experienced by adolescents and E-types [ 174 , 175 ]. The sleep phase delay in adolescents on weekends is a well-known phenomenon; however, the problem appears to start already during the preadolescence phase [ 176 ].…”
Section: Resultsmentioning
confidence: 99%